Konflik dan Integrasi Palang Putih Nusantara (PPN) Kejawen Urip Sejati di Onggosoro, Desa Giritengah, Kecamatan Borobudur, Kabupaten Magelang Tahun 1992 hingga 2022 - Angga, Vicky Verry (Keraton: Journal of History Education and Culture, 2023)
This article describes the history of the journey of PPN Kejawen Urip Sejati members in Onggosoro who experienced conflict until they reached an integration with their environment. Onggosoro residents have been involved in the embryonic organizations of PPN Kejawen Urip Sejati since the 1930s. Onggosoro residents were actively involved in social, cultural, economic and political activities in various embryonic organizations of PPN Kejawen Urip Sejati. In the 1990s, PPN Kejawen Urip Sejati was officially founded as an organization which was then followed by Onggosoro residents. The members of PPN Kejawen Urip Sejati in Onggosoro gave up their religious identity and chose to be believers. Conflicts with the general public cannot be avoided, until physical violence occurs against Kejawen Urip Sejati PPN members in Onggosoro. Kejawen Urip Sejati PPN members managed to make accommodation so that they were able to live in harmony and respect each other with their environment. This article is analyzed using the historical method which begins with the process of heuristics, source criticism, interpretation, and historiography or writing. The sources of writing are obtained from interviews, journals, books, and online media.